A field guide to current advances in paediatric movement disorders. Issue 4 (August 2015) - Silveira-Moriyama, Laura; Lin, Jean-Pierre
Abstract : Purpose of review: Recent advances in neurogenetics, neuroimmunology and nonpharmacological treatments have reshaped the field of paediatric movement disorders. In this review, we put recent findings into context providing a framework to enable navigation of the expanding literature in this field. Recent findings: Anti-NMDA receptor encephalitis has proven to be a significant cause of treatable movement disorder in children and to present a multifaceted link with herpes simplex encephalitis. The growing use of next-generation sequencing in both research and clinical practice has unravelled an expanding number of genes related to paediatric movement disorders as well as expanding spectrums of variable expressivity and phenotypic pleiotropy for various genes. Behavioural therapies have been proven efficacious in Tourette's syndrome and are likely to be helpful in complex motor stereotypies. Management of dystonia remains a clinical priority and challenge. Summary: The rapid advance of translational medicine has had major impacts on the field of paediatric movement disorders including diagnosis and treatment of these conditions. Video abstract: http://links.lww.com/CONR/A32 Abstract : Supplemental Digital Content is available in the text